2022
DOI: 10.20998/2522-9052.2022.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of the passage of audio signals in network-based audio analytics systems

Abstract: Relevance. Nowadays, more and more audio and video analytics systems work together. But in many cases, it is necessary to quickly transfer the audio stream. Therefore, the task of reducing delays in transmission of audio streams in network-based audio analytics systems becomes relevant. The object of research is the process of audio signal transmission. The subject of research is mathematical models of audio and video streams in network systems. The purpose of this paper is to develop a mathematical model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the case of using the optimization equation ( 5), optimization algorithm of the 3-node network [1] generally coincides with the algorithm discussed above. The difference is only in the procedure for determining the links bundle capacity of the path of the first choice 1 V by the value of the derivative 1 H  .…”
Section: Optimization Of the Network Structure In An Audio Analytics ...mentioning
confidence: 90%
See 4 more Smart Citations
“…In the case of using the optimization equation ( 5), optimization algorithm of the 3-node network [1] generally coincides with the algorithm discussed above. The difference is only in the procedure for determining the links bundle capacity of the path of the first choice 1 V by the value of the derivative 1 H  .…”
Section: Optimization Of the Network Structure In An Audio Analytics ...mentioning
confidence: 90%
“…The conducted studies [1] revealed that when solving optimization equations for basic structures, it is advisable to use the approximations proposed in [8] to optimize the link switching network of a hierarchical structure, because they make it possible to take into account modularity of transmission systems, structure of the switching field and the connection establishment algorithm, and, at the same time, significantly reduce number of calculations.…”
Section: The Methods Of Choosing Network Structure For An Audio Analy...mentioning
confidence: 99%
See 3 more Smart Citations